'In or Out'—On the Dynamic between Acceptance and Rejection and its Influence on Health in Adolescent Girls. (August 2014) - Flacking, Renée; Jerdén, Lars; Bergström, Erik; Starrin, Bengt
Adolescent girls' subjective health, or well-being, is of international concern as the frequency of psychological and psychosomatic complaints is continuously increasing in several countries world-wide. The causes of this development are still obscure. The aim of this study was to explore well-being and strategies for increased well-being among adolescent girls. Grounded Theory method was used, in which in-depth interviews were held with 18 adolescent girls, 17–18 years of age. Results showed that striving for acceptance and avoiding rejection were central for their well-being. When rejection was experienced, emotions of stress–shame were recognized, a phenomena we call the stress–shame cycle. In the struggle to prevent rejection and to become accepted, the girls strived to boost their social attractiveness by impression management.